Ugaritic and Hebrew poetic parallelism: a trial cut ; (ʿnt I and Proverbs 2) - Pardee, Dennis (Supplements to Vetus Testamentum, 1988)
Preliminary material -- Chapter One: The Parallelistic Structure of ‘nt I3 -- Chapter Two: The Parallelistic Structure of Proverbs 2 -- Chapter Three: A Comparison of Ugaritic and Hebrew Parallelism -- Appendix I: Ugaritic and Hebrew Poetry: Parallelism -- Appendix II: Types and Distributions of Parallelism in Ugaritic and Hebrew Poetry -- Index of Biblical Passages.